SISTEM PAKAR MENDIAGNOSA PENYAKIT PADA UNGGAS DENGAN METODE TEOREMA BAYES BERBASIS WEB - Achmad Rido'i; Retno Wardhani; Masruroh masruroh (Universitas Islam Lamongan, 2017)
Poultry has many benefits such as its eggs and meat that cannot be separated from the needs of daily consumption. However, there is a major problem that almost experienced every year for the breders. The disease in poultry is a serious problem that becomes obstacles for the breeders. Based on this problem, the application maker made an expert system application to diagnose the disease in poultry with Bayes theorem method. This application is expected to help the breeders in diagnosing the disease in poultry, therefore the death of poultry can be minimized. This application has been successfully designed and implemented using notepad ++ and php MySQL through several steps of main menu design system, those are; consultation, diseases, and aid. The coding making is done in notepad ++ application. Then making the database is done in php MySQL. The result reveals that this application is made to identify the disease based on the existing symptoms. In testing, 10 breeders stated that this application can help diagnose the disease in poultry.